Catalytic cracking and aromatization of C4 - C5 hydrocarbons over ZSM-5 zeolite: acitivity and regeneration - Prancharee Teerathanakit (Chulalongkorn University, 2014)
Thesis (M.Sc.) -- Chulalongkorn University, 2006